Pastoral system rejuvenated - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Turkana pastoralists have found that water harvesting has taken the risk out of growing sorghum. Indeed, in many years they can get two crops a year and food supplies are much more secure than they have been in the past. After the severe drought of...